1996
DOI: 10.1016/s0166-4328(97)81112-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of site-specific injections into the basal forebrain on water maze and radial arm maze performance in the male rat after immunolesioning with 192 IgG saporin

Abstract: In this study, we investigated the effects of 192 IgG saporin injections into the medial septal area (MSA), or nucleus basalis magnocellularis (NBM), and combined injections into the MSA and NBM, on water maze and radial arm maze performance in the male rat. The results of the present study reveal a dissociation between the effects of 192 IgG saporin injections into the basal forebrain on the performance of two tasks of spatial learning in the rat. Bilateral injections of 192 IgG saporin into the NBM, MSA or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
72
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 48 publications
12
72
1
2
Order By: Relevance
“…This demonstrates that a mild aversive stimulus can attenuate or mask a deficit resulting from lesion of MS cholinergic neurons on acquisition of a spatial task. This is consistent with studies of working memory which used paradigms with an aversive component and that found that selective cholinergic lesions of the MS did not produce acquisition deficits in spatial working memory [4,5,16]. Notably, application of the aversive stimulus had no significant effect on DMP acquisition in the non-lesioned controls.…”
Section: Effects On Dmp Acquisitionsupporting
confidence: 90%
See 1 more Smart Citation
“…This demonstrates that a mild aversive stimulus can attenuate or mask a deficit resulting from lesion of MS cholinergic neurons on acquisition of a spatial task. This is consistent with studies of working memory which used paradigms with an aversive component and that found that selective cholinergic lesions of the MS did not produce acquisition deficits in spatial working memory [4,5,16]. Notably, application of the aversive stimulus had no significant effect on DMP acquisition in the non-lesioned controls.…”
Section: Effects On Dmp Acquisitionsupporting
confidence: 90%
“…Other investigations, though, have reported only limited effects of MS SAP lesions in other spatial tasks. For example, Dornan et al [16] reported that a selective reduction of cholinergic transmission in the basal forebrain was by itself insufficient to account for the functional impairments in spatial learning of rats using a Morris water maze (MWM) paradigm. Baxter et al [4,5], also utilizing a MWM task, reported similar findings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for some investigators cholinergic lesions did not cause impairment in spatial memory (15,23). Spatial memory, determined by the MWM, has been associated with LTP in mice in vivo (5).…”
mentioning
confidence: 98%
“…These studies have given inconsistent results concerning the cognitive and behavioral processes that are affected by altering cholinergic transmission (12,15,16). This is likely related to the fact that in many cases both noncholinergic and cholinergic projection neurons are destroyed, or that the lesions produced do not fully deplete cholinergic neurons.…”
mentioning
confidence: 99%
See 1 more Smart Citation